Techno-economic analysis of combined heat pump and solar PV system for multi-family houses: An Austrian case study. (July 2021) - Schreurs, Twan; Madani, Hatef; Zottl, Andreas; Sommerfeldt, Nelson; Zucker, Gerhard
Abstract: With the increasing amount of building renovations in Austria, the potential increases for replacing conventional national gas heating systems with heat pumps (HP) and thereby reduce CO2 emissions particularly when combined with solar photovoltaics (PV). The Austrian subsidization scheme for HP and PV systems are different for every state, creating confusion and inconstancy for potential adopters. This study provides a parametric techno-economic analysis of PV + HP systems to identify the critical economic parameters on profitability and make policy recommendations. A case study in Vienna is modelled using demand from the Building Model Generator and black box efficiency models for the HP and PV simulated with hourly time steps. The results show that both air-source and ground source heat pumps are currently profitable with PV under current subsidy schemes. The benefit-to-cost ratio (BCR) is highly influenced by capital costs and subsidies, however natural gas prices have the greatest influence. Increasing natural gas prices by 0.01 €/kWh, or 17%, is enough to replace all other complicated subsidies for both HP and PV. This is equivalent to a carbon emissions price of 33 €/ton and could result in a reduction of CO2 emissions in multi-family houses by approximately 45%–60%. Highlights: A techno-economic analysis is carried out on combined heat pumps and solar PV systems, using Austria as a case study. A holistic system modeling approach is used to evaluate annual technical performance and life cycle cost effectiveness. Any increase in gas prices makes heat pump with PV systems more cost effective, even without subsidies. Replacing gas heating with heat pumps and PV in European multifamily houses reduces CO2 emissions. The results motivate a simpler carbon tax policy to replace the complicated patchwork of PV and heat pump subsidies.